2019
DOI: 10.3390/genes10100757
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Early European Neolithic Dog Dispersal: New Data on Southeastern European Subfossil Dogs from the Prehistoric and Antiquity Ages

Abstract: The history of dog domestication is still under debate, but it is doubtless the process of an ancient partnership between dogs (Canis familiaris) and humans. Although data on ancient DNA for dog diversity are still incomplete, it is clear that several regional dog populations had formed in Eurasia up to the Holocene. During the Neolithic Revolution and the transition from hunter-gatherer to farmer societies, followed by civilization changes in the Antiquity period, the dog population structure also changed. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 44 publications
(122 reference statements)
6
21
0
Order By: Relevance
“…Those results, combined with the findings of Pires et al [33] on the occurrence of Late Pleistocene wolves and Mesolithic dog carrying a Hg A canine haplotype in another glacial refugium, the Iberian Peninsula, stimulate interest towards these areas and their role in the dog domestication issue as a whole. Neolithic Bulgarian dogs in the Balkan Peninsula [6] with high percentages of Hg A and B support the findings of Pires et al [33]. These results are of particular interest because, according to previous data [36], Hg A-dogs were only estimated to have arrived in Europe during the Bronze Age.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Those results, combined with the findings of Pires et al [33] on the occurrence of Late Pleistocene wolves and Mesolithic dog carrying a Hg A canine haplotype in another glacial refugium, the Iberian Peninsula, stimulate interest towards these areas and their role in the dog domestication issue as a whole. Neolithic Bulgarian dogs in the Balkan Peninsula [6] with high percentages of Hg A and B support the findings of Pires et al [33]. These results are of particular interest because, according to previous data [36], Hg A-dogs were only estimated to have arrived in Europe during the Bronze Age.…”
Section: Introductionsupporting
confidence: 82%
“…Electropherograms were analyzed and edited using the software FinchTV (Geospiza Inc., Seattle, WA, USA) and BioEdit [49,50]. Sequences were aligned using the dog mtDNA sequences NC_002008 and EU789787 as reference, following the steps of previously published papers [6,9,51,52]. Haplogroup assignments were determined through a phylogenetic analysis by creating UPGMA trees in MEGA X (Penn State University, PA, USA) [53], using reference samples with well-defined dog matrilines, available from previous studies [54,55].…”
Section: Haplotype Identification and Phylogenetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of mtDNA in European pre-Neolithic dogs found all 15 investigated samples (100%) to have haplotypes belonging to haplogroup C [19]. In contrast, a study of 16 Neolithic dogs from Southeast Europe showed "normal" frequencies of haplogroup A and B (75% and 20%, respectively) and no haplotype from haplogroup C [20]. Our study similarly shows that today's European dogs carry all three major haplogroups, A, B and C, with only 8% carrying haplotype C (Table 1).…”
Section: Discussionmentioning
confidence: 97%